An ecological history of modern China - Harrell, Stevan (Seattle : University of Washington Press, 2023)
"An Ecological History of Modern China is the first attempt at a comprehensive and conceptually coherent account of the process of development in modern China, from the perspective not of the economy but of the biophysical world. This book shows that development in China is desirable in many ways, but that there is a cost in environmental degradation. Specifically, the book addresses the question of how agricultural, industrial, and urban development have affected the resilience of China's ecosystems-their ability to withstand disturbances and further growth"--
Introduction: Understanding China through its ecological history -- Part I. Setting the scene. A tour of China's social-ecological systems -- Development, revolution, and science -- Part II. Land, water, and food. Feeding a starving nation, 1949-1957 -- Three years of natural disasters, 1958-1961 -- Normal socialist agriculture, 1962-1978 -- Solving the warm and full problem, 1978-1998 -- Every last drop, 1998-2022 -- Damned if you do, 1993-2021 -- A toxic cornucopia, 2000-2022 -- Big ag and its ecosystem effects, 2002-2022 -- Part III. Cities and industry. A revolution of steel, 1949-1961 -- Normal socialist industry, 1962-1980 -- Factory to the world, 1984-2015 -- Building an urban continent, 1980-2022 -- Sludge abides, 1990-2022 -- Paradoxes of eco-development, 1998-2022 -- Conclusion: Chinese history as ecological history.
Online resource title from digital title page (viewed on August 23, 2023).
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Environmental sciences -- China; Economic development -- Environmental aspects -- China; Ecology -- China; Environmental policy -- China; Sciences de l'environnement -- Chine; Développement économique -- Aspect de l'environnement -- Chine; Environnement -- Politique gouvernementale -- Chine; SOCIAL SCIENCE / Ethnic Studies / Asian Studies; Ecology; Economic development -- Environmental aspects; Environmental policy; Environmental sciences; China; Ecologia; Política ambiental; Desenvolupament econòmic.; Xina; Electronic books; Llibres electrònics.